STRENGTH ANALYSIS OF BANDED ROLL FOR ASYMMETRIC ROLLING - L. A. Isaevich; D. M. Ivanickij; M. I. Sidorenko (Литьë и металлургия, 2016)
The calculation of the nominal torque on the rolls during asymmetric rolling of a strip with small laminated springs are held. To stabilize the rolling process it is proposed to use a front tension and a certain minimum value was calculated. Misalignment of the circumferential speeds of the driving and driven rolls are calculated. The design of a composite roll banded with two tabs on the brace and the two grooves on the shaft are proposed. Crumpling test and shear test of the tabs on the brace were conducted. Necessary structural toughness was provided.